2015
DOI: 10.1007/s10519-015-9754-2
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Adolescent Physical Fitness: A Multivariate Approach and Meta-analysis

Abstract: Physical fitness can be defined as a set of components that determine exercise ability and influence performance in sports. This study investigates the genetic and environmental influences on individual differences in explosive leg strength (vertical jump), handgrip strength, balance, and flexibility (sit-and-reach) in 227 healthy monozygotic and dizygotic twin pairs and 38 of their singleton siblings (mean age 17.2 ± 1.2). Heritability estimates were 49 % (95 % CI 35–60 %) for vertical jump, 59 % (95 % CI 46–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 36 publications
6
35
1
1
Order By: Relevance
“…Most recently, heritability estimates of grip strength (N=874) and jumping ability (N=4516) in adolescents and young adults (mean age 17.2 ± 1.2 years old) using metaanalysis have been reported as 63% and 62%, respectively. 31 These values were consistent with H 2 -msp from studies involving subjects <20 years old in the present study. In addition, the sensitivity analysis of our meta-analysis showed no relationship between the H 2 -msp and sex (P=.115).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Most recently, heritability estimates of grip strength (N=874) and jumping ability (N=4516) in adolescents and young adults (mean age 17.2 ± 1.2 years old) using metaanalysis have been reported as 63% and 62%, respectively. 31 These values were consistent with H 2 -msp from studies involving subjects <20 years old in the present study. In addition, the sensitivity analysis of our meta-analysis showed no relationship between the H 2 -msp and sex (P=.115).…”
Section: Discussionsupporting
confidence: 91%
“…Recently, Schutte et al 31 reported the weighted mean heritability of physical fitness in adolescents and young adults using meta-analysis. They showed that heritability estimates for vertical jump (five measurements) for 62%, hand grip strength (five measurements) for 63%, flexibility (five measurements) for 50%, and balance (four measurements) for 35%.…”
Section: Introductionmentioning
confidence: 99%
“…In relation to sex, no differences between boys and girls were found, as it has been reported in other studies [22,43]. In contrast, with regards to the PF test, as occurred in a large number of studies, boys scored higher than girls; as well as for the case of PA level.…”
Section: Discussionsupporting
confidence: 62%
“…In contrast, with regards to the PF test, as occurred in a large number of studies, boys scored higher than girls; as well as for the case of PA level. This disparity in results according to sex may be related to the different moments and levels of evolutionary development, since these may determine a greater performance of the males in the PF tests [46].…”
Section: Discussionmentioning
confidence: 99%